Diagnosis of Collagen Type III Glomerulopathy Using Picrosirius Red and PASH/Masson's Trichrome Stain. Issue 5 (September 2020) - Davis, Katelin L.; Burnum, Anne L.; Beck, Jessica A.; Kirejczyk, Shannon G. M.; Miller, Margaret A.; Sola, Mario F.; Brown, Cathy A.
Canine collagen type III glomerulopathy (Col3GP) is a rare juvenile nephropathy in which irregular type III collagen fibrils and fibronectin accumulate in glomerular capillary walls and the mesangium. Necropsy findings were reviewed from 5 puppies diagnosed with Col3GP at 6 to 18 weeks of age. Histologically, with hematoxylin and eosin stain, the glomerular capillary walls and mesangium were diffusely and globally expanded by homogeneous pale eosinophilic material. Ultrastructurally, the subendothelial zone and mesangium were expanded by fibronectin and cross-banded collagen type III fibrils, diagnostic of Col3GP. Two additional stains were employed to identify the material within glomeruli as fibrillar collagen using light microscopy. In all 5 cases, the material was red with picrosirius red and birefringent under polarized light, and was blue with periodic acid-Schiff/hematoxylin/trichrome (PASH/TRI), thereby identifying it as fibrillar collagen. Based on these unique staining characteristics with picrosirius red and PASH/TRI, Col3GP may be reliably diagnosed with light microscopy alone.